Latent structure and factorial invariance of the Cognitive Emotional Regulation Questionnaire in Peruvian schoolchildren - Barrios Sallo, Zoraida (2023)
The latent structure and factorial invariance of the CERQ were identified by studying a sample of 430 Peruvian schoolchildren from five state institutions in Lima, Peru. A confirmatory factor analysis of the instrument was carried out and the internal consistency of each dimension was analyzed. Then, the hypothesis of factorial invariance of the final version according to the gender of the participants was hypothesized. The results indicate a latent structure of nine factors of which the proposed version showed a favorable goodness of fit (RMSEA = 065, SRMR = .069, CFI = .917, GFI = .972, NFI = .949) with good to acceptable internal consistency coefficients. Likewise, from the CFAMG approach, evidence was obtained for weak, strong and strict factorial invariance. It is concluded that the CERQ has a defined latent structure and can be used with both men and women.